Natural Treatments of Oligomenorrhea based on Persian Medicine - Farnoush Falahat; Mandana Tavakkoli; Roshanak Mokaberinejad; Sedigheh Ayati; Zohre Feyzabadi (Mashhad University of Medical Sciences, 2018)
Introduction: Oligomenorrhea is one of the most common menstrual disorders defined as the prolongation of menstrual intervals. This growing disorder reduce the quality of life for women of reproductive age due to complications, such as abnormal uterine bleeding, infertility, hirsutism and psycho-social consequences. Due to the complications of hormonal medications which are the common treatment of this disorder, the necessity of using complementary therapies is suggested; therefore, the present review study was conducted to investigate the therapeutic strategies of Persian medicine. Methods: In this review study, the main sources of Persian Medicine were investigated using the synonyms of oligomenorrhea such as "Ehtebās-e-tams", "Habs-e- heiz", reduction and discontinuation of menstruation. Then, to find new studies, the databases such as Google scholar, PubMed and ISI were searched with the keywords of Oligomenorrhea, Amenorrhea, PCOS, Persian Medicine and Traditional Medicine and the results were compared. Results: In texts of Persian Medicine, oligomenorrhea is referred as the "Ehtebas Tams". Therapeutic approaches to "Ehtebas Tams", like other treatments in Persian Medicine, in the first step include lifestyle modification, dietary modification, sleep and wake adjustment, exercise and bathing. The second step includes the use of emmenagogue herbal medicine which are mostly considered as phytoestrogen. These herbs are prescribed in various forms (Pill, Decoction, Herbal Tea, Vaginal Suppository, Vaginal Douche, ointment and sitz-bath). In the third step, manipulations such as wet cupping and phlebotomy are recommended as a therapeutic approach. Conclusion: Considering the effectiveness of some of these treatments in new studies such as Vitex agnus-castus, Mentha longifolia and Foeniculum vulgare, it is recommended to conduct more clinical studies based on Persian medicine therapies in addition to conventional medicine for treatment of oligomenorrhea.